Strength shoes: Pain, no gain? - Hatfield, F. C. (Sportscience)
Summary: A recent study found similar small gains (~1%) in sprint and jump performance when previously untrained young men trained for 10 weeks in regular shoes or Strength Shoes. Injury rate was much higher with Strength Shoes, probably a result of the inappropriate training program prescribed by the manufacturer. An earlier study of more experienced athletes showed trends towards better performance and less injury with normal shoes. I therefore cannot recommend Strength Shoes. I have had considerable experience with Strength Shoes, and with training athletes using them. My impression up until now has been that these shoes might enhance performance of experienced athletes if they are used with the right kind of training program. But the research to date indicates that the right kind of training program might produce even better results with normal shoes. I cannot recommend Strength Shoes.